CPM 3. Closing the Yield Gap of in the Philippines through Site Specific Nutrient Management (The Philippine Journal of Crop Science, 2018)
Increasing demand in the food and the feed industry for cassava has made it first in terms of area harvested among root crops and other staple vegetables in the Philippines (PSA 2017). However, due to lack of appropriate fertilizer practice, the mean fresh root yield of cassava in the country was only 12.51 (tons/ha), way below that of 32.68 of Laos, the highest in South East Asia (FAO,, 2018). To increase Philippine cassava yield without undermining soil sustainability, this study aimed to determine the cassava yield responses to fertilization as influenced by variety, and to show the efficiency of SSNM (site-specific nutrient management)-based fertilization for cassava. Four fertilization treatments namely, full NPK rate (200-100-350), cassava national fertilizer recommendation/NFR (56-56-56), SSNM prototype (180-70-250), and unfertilized control as main plots and two varieties as subplots in split-plot design were established in 54 sites from 15 regions using a total of 17 locally-available varieties. Highest fresh tuber yield mean was attained by the SSNM (33.83 tons/ha) without significant difference to that of full NPK (32.76), surpassing NFR (29.98) and attaining 7.01 t/ha (26.23%) difference over that of unfertilized control. Differences in fresh root yield across treatments were influenced by variety and location. Results also confirmed that cassava heavily consumes K, followed by N and then P. Variety also affects N and K removal. Despite the medium to high soil fertility of all sites, cassava still responded to fertilization. The SSNM prototype yield surpassed full NPK and NFR by 3.2% and 13.8% respectively. As such, SSNM based fertilization is an efficient way for cassava fertilization. By optimizing the SSNM recommendation based upon the influence of variety and site characteristics, appropriate quick fertilizer guides can be developed to increase cassava production in the country.